Orfandad y su incidencia en el bienestar emocional de un beneficiario de 19 años en situación de calle de la Fundación RESADE Guayaquil - Aroca Zambrano, Mishelle Gabriela (2022)
Orphanhood is a condición in which the minor loses due to the death for one of his parents or both, this is a social factor that has a direct impact on the individual, whether in the emotional, social or economic area. On the other hand, emotional well-being is a state in which the individual perceives a personal harmony between their emotions and the self. The present case study is developed with the objective of analyzing how orphanhood affects the emotional well-being of a 19-year-old beneficiary of the RESA Foundation of Guayaquil, with the purpose of elaborating a proposal for psychological intervention from the cognitive behavioral approach to help achieve the emotional well-being of this user in the event that he is really affected. For this, psychological techniques and tools were used in order to gather information that gave us an orientation on how to approach the case and after them, elaborate the therapeutic intervention plan based on Beck's cognitive behavioral therapy, in which we detected automatic thoughts, which based on the theory, they are the ones that generate the disturbance to the individual. Finally, we apply cognitive restructuring in order to change the individual's thoughts so that they achieve emotional well-being and also meet the objective of the foundation where they are staying, which is their reintegration into the labor-social market.